SAT0194 Hplc method for pentosidine determination in urine and serum. (1st June 2001) - Spacek, P; Adam, M
Abstract : Background: Pentosidine (PEN) is the most known representative from the so-called AGE derivatives, whose concentration is elevated in some pathological conditions, 1 (e.g. in diabetes, renal failure, osteoarthritis (OA), inflammatory diseases, etc.). PEN determination is therefore often used for characterisation of the disease activity. Objectives: The aim of this study is to elaborate precise and sensitive HPLC method for PEN determination, apply it the for evaluation in urine samples in the OA patients and in healthy controls, and to test possible correlation between urine pyridinoline 2 and pentosidine. Methods: Liquid chromatograph of the firm SHIMADZU type CLASS VP version 5.0 was on line controlled by means of special software in Windows 98 milieu. Glass column Separon SGX C18, 150 × 3 mm (Tessek, Prague, Czech Republic) as the stationary phase and mobile phase 0.02 M heptafluorobutyric acid (HFBA), 0.01 M (NH4)2SO4 with variable acetonitrile (ACN) concentration was used. Results: Pentosidine standard was synthesised utilising simple polymer analogical reaction and kindly quantified by HPLC in foreign lab. 3 Variation in the reproducibility (RSD) of the HPLC alone was slightly above 1%, RSD of the whole method (i.e. including sample hydrolysis and purification) was 4.44%, recovery was 77 ± 3.5%, HPLC sensitivity limit was 17.6 femtomoles. Urine PEN concentrations were determined in the OA patients (N = 37, age 66.97 ± 9.89 years) and in control individuals (N = 15, age 30.01 ± 8.67 years). PEN-age dependence was eliminated by extrapolation in the sense of known measured PEN-age dependence. 4 In OA PEN urine concentrations were significantly higher (almost four times) compared with healthy controls (8.0 ± 7.2 vs. 2.1 ± 0.5 nmol/mmol creat., P = 0.00002). Slight correlation exists between urinary pentosidine and urinary pyridinoline in OA (U-PEN = 0.0773*U-PD +2.2595, r = 0.4), probably partially evoked by immunity response of the organism due to the toxic action of PEN-containing molecular domains, 5, 6 s ary leading to accelerated resorption kinetics and thus to the additional increasing pyridinoline level. Conclusion: Sensitive and accurate HPLC method for pentosidine determination was elaborated, optimised and quantified with prepared PEN standard. Urine samples of OA patients and healthy controls were evaluated. Results can probably yield useful additional information about activity of the disease. References: Sell DR, Monnier VM. J Biol Chem. 1989;264(36):21697–702 paèek P, Hulejová H, Adam M. J Liq Chrom Rel Technol. 1997;20(12):1921–30 VM Monnier, Sell DR. Case Western Reserve University, Cleveland, OH 44106 Takahashi M, Suzuki M, Kushida K, Miyamoto S, Inoue T. Br J Rheumatol. 1997;36 :637–42 Vlassara H. Diabetes 1997;46(2):S19-25 Sullivan R. Arch Physiol Biochem. 1996;104(7):797–806